2013
DOI: 10.4103/0974-7796.115731
|View full text |Cite
|
Sign up to set email alerts
|

Role of ureteric stents in relieving obstruction in patients with obstructive uropathy

Abstract: Purpose:The aim of this study is to evaluate the role of ureteric stents in relieving obstruction and improvement of kidney function in patients with obstructive uropathy.Materials and Methods:This study involved 138 patients with obstructive uropathy with age ranged from 2 months to 73 years. Patients classified into two groups: Group (I): Includes 57 patients (41.3%), ureteric stents fixed to them; and Group (II): Includes 81 patients (58.6%) managed by other treatment modalities. All patients underwent clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In addition to the above two, few also believe in stenting the un-operated renal unit to prevent any further functional deterioration during the waiting time [ 7 ]. In complicated cases presenting as urosepsis or large mass causing respiratory distress, temporizing procedures such as percutaneous nephrostomy (PCN) and cystoscopy may be required for relieving the obstruction [ 7 , 9 ]. Shehab et al have demonstrated significant improvement in the renal function and clinical condition of the patients with obstructive uropathy following ureteral stenting [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above two, few also believe in stenting the un-operated renal unit to prevent any further functional deterioration during the waiting time [ 7 ]. In complicated cases presenting as urosepsis or large mass causing respiratory distress, temporizing procedures such as percutaneous nephrostomy (PCN) and cystoscopy may be required for relieving the obstruction [ 7 , 9 ]. Shehab et al have demonstrated significant improvement in the renal function and clinical condition of the patients with obstructive uropathy following ureteral stenting [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In complicated cases presenting as urosepsis or large mass causing respiratory distress, temporizing procedures such as percutaneous nephrostomy (PCN) and cystoscopy may be required for relieving the obstruction [ 7 , 9 ]. Shehab et al have demonstrated significant improvement in the renal function and clinical condition of the patients with obstructive uropathy following ureteral stenting [ 9 ]. In the index case (case no 2), retrograde stenting was not successful on the more severely obstructed side.…”
Section: Discussionmentioning
confidence: 99%